Chinese college students' English linguistic proficiency, attitude and expository writing competence - Shen Shuxia (2006)
The study was undertaken to investigate writing in an EFL context. It focused on the relationships between Chinese college EFL learners' English linguistic proficiency, writing attitude, and their English expository writing competence. Thirty randomly selected college students participated in this study. They were native Chinese who learned English as a foreign language by receiving formal instructions. The data were collected at Huaqiao University. It was concluded that Chinese college EFL learners' English language proficiency has a positive effect on their expository writing competence.
"March 2006."
Thesis (M.A. Education : Language Education)--University of the Philippines, Diliman.
Keywords: Huaqiao University (China) -- Students; English language -- Study and teaching (Higher) -- Chinese; English language -- Rhetoric -- Study and teaching (Higher) -- China